IMPROVING THE ABILITY IN WRITING PARAGRAPH AT THE SECOND GRADE STUDENTS OF SMK NEGERI 5 PINRANG THROUGH PARAPHRASING TECHNIQUE - Lestari, Siti; Nurhamdah, Nurhamdah (Inspiring: English Education Journal, 2019)
This study is to see improving writing ability at the second grade students of SMK Negeri 5 Pinrang through Paraphrasing Technique. It aimed to know whether Paraphrasing Technique can improve the students? Writing Ability in Writing Paragraph. The subject of this research is XI TGB class which is consisted of 17 students. The sample was taken by using random sampling. The design in this research was pre-experimental with pre-test and post-test design. The students did the pre-test, got the treatment and did the post-test. The result in this research was indicated that there was improvement of the students? Writing Ability. It was indicated by the students? mean score of post-test (81.48) was greater than pre-test (50.58). Even, for the level significant (p) 5% and df = 17, and the value of table is 1.746, while the value of t-test is 14,26. it means that, the t-test value is greater than t-table (14,26 ? 1.746). Thus, it can be concluded that the students? Writing ability in writing paragraph is significant better after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is fail rejected.